Application of multicultural nursing in a patient with giant left ventricular pseudoaneurysm (1例左心室巨大假性室壁瘤患者的多元文化护理) - LI Die (李蝶); LI Ke (李珂); ZHOU Yun (周云); LI Feng (李凤) (Association of Integrative Nursing, 2023)
This paper summarized the multicultural nursing management for a patient with giant left ventricular pseudoaneurysm. Based on the self-management and clinical application of postoperative power-assisted enveloped-type special garment, health guidance and nursing interventions were carried out to improve the clinical outcomes of the patient and avoid the rupture of the pseudoaneurysm. During the perioperative period, the multicultural nursing theory was used to analyze the advantages and disadvantages of self-management. Aiming for prevention of adverse factors, the multicultural nursing team led by the primary nurse participated in the formulation of patient self-management, provided nursing care consistent with the patient's culture and health education, and made full preparation for the patient with standardized nursing behavior. (本文回顾1例左心室巨大假性室壁瘤(LVPA)患者的多元文化护理体会。为患者制定自我管理目标和方案, 应用实用新型专利(术后助力环抱式专用衣)提升术后患者伤口恢复及自理能力, 护理人员给予引导和积极干预, 患者各方面得到改善, 避免巨大LVPA破裂的发生。围手术期运用多元文化护理理论, 分析自我管理的有利因素和不利因素, 针对不利因素目标分析, 以责任护士为主导的多元文化护理团队参与制定患者的自我管理, 提供与患者文化相一致的护理以及健康教育工作, 以规范的护理行为, 为患者做好充分术前准备, 促进术后康复。)